Development of magnesium implants by application of conjoint‐based quality function deployment - Siefen, Sarah; Höck, Michael (Journal of biomedical materials research. Part A, 2019)
Biodegradable magnesium‐based implants are the subject of a great deal of research for different orthopedic and vascular applications. The targeted design and properties depend on the specific medical function and location in the body. Development of the biomaterial requires a comprehensive understanding of the biological interaction between the implant and the host tissue, as well as of the behavior in the physiological environment in vivo. Research into and the development of innovative magnesium implants entails interdisciplinary research efforts and communication between materials science, bioscience, and medical experts. The present study provides a transparent planning and communication tool for market‐oriented implant development processes. The objective was to identify medical needs at an early stage of the development process and to quantify the importance of the engineering characteristics of different research fields that cater to specific implant requirements. The method is demonstrated by the performance of a survey‐based conjoint analysis, which was integrated into a quality function deployment approach. Twenty‐seven medical professionals and 29 biomaterial scientists assessed the importance of identified medical requirements, whereby the control of mechanical integrity and degradation along with nontoxicity and nonimmunogenicity showed the highest number of preferences. The evaluation of implant options by 31 experts indicated that the engineering characteristic with the highest importance was the condition and sterilization of the surface. These values can be used to set priorities in strategic decisions. Research trials can be aligned to medical preferences, ensuring high product quality and an effective development process. This is the first paper to report on the application of conjoint‐based quality function deployment in biomaterial research.